Adnan S.AbdulNabi Inhibition of Carbon Steel Acid Corrosion Using Vanillin - AbdulNabi , Adnan (University of Thi-Qar Journal of Science, 2019)
The inhibition action of the corrosion of carbon steel in hydrochloric acid solution by vanillin has been studied using weight loss technique. Inhibition was found to increase with increasing inhibitor concentration and decreasing temperature. A first order mechanism has been deduced from the kinetic treatment of the weight loss results and the process of inhibition was attributed to physiosorption. The results obtained showed that vanillin could serve as an effective inhibitor of the corrosion of carbon steel in hydrochloric acid media.